2013
DOI: 10.1111/ijfs.12386
|View full text |Cite
|
Sign up to set email alerts
|

Structure, trypsin inhibitor activity and functional properties of germinated soybean protein isolate

Abstract: Summary The objective of this research was to investigate the effects of germination on functional and conformational properties as well as the in vitro trypsin digestibility of soy protein isolate (SPI). The influences of germination on the molecular properties of SPI were also evaluated. The germination degraded lipoxygenase, α, α' subunits of β‐conglycinin (7S) and acidic chains of glycinin (11S) of soybean. Concomitantly, the loss of tertiary structures of SPI occurred due to the germination. The trypsin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…As far as we know, there was no study evaluate the droplet size of GSB milk. In our study, a bigger droplet size of GSB milk could be related to the unfolding and the breaking of peptide bond due to the endogenous proteases activated by germination (Aijie et al, 2014;Gao et al, 2019;Puteri et al, 2018). The authors suggested that the germination process could increase the hydrophilic capacity of soy protein while decreasing its surface hydrophobicity, resulting in a bigger droplet size.…”
Section: Droplet Size Distribution and Rheological Properties Of Soymilk And Gsbs Milkmentioning
confidence: 58%
See 1 more Smart Citation
“…As far as we know, there was no study evaluate the droplet size of GSB milk. In our study, a bigger droplet size of GSB milk could be related to the unfolding and the breaking of peptide bond due to the endogenous proteases activated by germination (Aijie et al, 2014;Gao et al, 2019;Puteri et al, 2018). The authors suggested that the germination process could increase the hydrophilic capacity of soy protein while decreasing its surface hydrophobicity, resulting in a bigger droplet size.…”
Section: Droplet Size Distribution and Rheological Properties Of Soymilk And Gsbs Milkmentioning
confidence: 58%
“…While the changes in legume composition during germination can improve nutrition value for raw material, it also leads to remarkable changes in sensory and physiological properties for food products (Aijie et al, 2014;Murugkar, 2014). For example, sensory properties of soymilk, soy-yogurt, and tofu prepared from GSB were evaluated as different with those prepared from soybean (Landfeld et al, 2014;Murugkar, 2014).…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Concurrently, the trypsin inhibitory activity (TIA) was reduced by germination, associated to protease-catalysed hydrolysis of lectins and trypsin inhibitors. Aijie et al [ 25 ] found a similar relation; however, the DH decreased, and the TIA increased for the longest germination times, which they explained by a resynthesis of trypsin inhibitors by photosynthesis. For black soybean, an inverse relation was observed: the PI produced from non-germinated seeds yielded the largest proportion of low molecular weight peptides [ 26 ].…”
Section: Ingredient Preparationmentioning
confidence: 78%
“…In this study, heating induced protein aggregation as well as pepsin during the gastric phase. The TIA of germinated soybean PI was reduced by the heat treatment [ 25 ]. Conversely, the apparent digestibility of heated, spray-dried and autoclaved pastes of soybean PI, determined in a rat assay, was significantly lower than that of non-autoclaved pastes [ 63 ].…”
Section: Post-fractionation Processingmentioning
confidence: 99%
“…Soy proteins have been widely used to formulate foods with a goal of improving their nutritional and functional qualities due to the high protein level and well-balanced amino acid composition (Aijie, Shouwei, & Li, 2014). However, soy is known by its allergenic power in children, and can be serious for them (Sicherer & Sampson, 2009).…”
Section: Introductionmentioning
confidence: 99%